2017
DOI: 10.1093/gbe/evx063
|View full text |Cite
|
Sign up to set email alerts
|

DNA Remodeling by Strict Partial Endoreplication in Orchids, an Original Process in the Plant Kingdom

Abstract: DNA remodeling during endoreplication appears to be a strong developmental characteristic in orchids. In this study, we analyzed DNA content and nuclei in 41 species of orchids to further map the genome evolution in this plant family. We demonstrate that the DNA remodeling observed in 36 out of 41 orchids studied corresponds to strict partial endoreplication. Such process is developmentally regulated in each wild species studied. Cytometry data analyses allowed us to propose a model where nuclear states 2C, 4E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 54 publications
2
32
0
Order By: Relevance
“…Analysing somaclonal variants of Phalaenopsis, Lee et al (2016) found that the degree of endoreduplication in the petals and flower stalks Mishiba and Mii, 2000 was higher in the variants than in control plants, and this corresponded with the diameter of the petal and the thickness of different organs, traits potentially desirable in orchid breeding. When applying FCM to analyse orchids, one must be aware, however, that in some Orchidaceae species partial endoreduplication occurs, which makes interpretation of the histograms challenging (Brown et al, 2017). One of the best recognized endoreduplication patterns in a fruit is that of S. lycopersicum (Pirrello et al, 2014, and references therein).…”
Section: Plant Growth and Developmentmentioning
confidence: 99%
“…Analysing somaclonal variants of Phalaenopsis, Lee et al (2016) found that the degree of endoreduplication in the petals and flower stalks Mishiba and Mii, 2000 was higher in the variants than in control plants, and this corresponded with the diameter of the petal and the thickness of different organs, traits potentially desirable in orchid breeding. When applying FCM to analyse orchids, one must be aware, however, that in some Orchidaceae species partial endoreduplication occurs, which makes interpretation of the histograms challenging (Brown et al, 2017). One of the best recognized endoreduplication patterns in a fruit is that of S. lycopersicum (Pirrello et al, 2014, and references therein).…”
Section: Plant Growth and Developmentmentioning
confidence: 99%
“…Overall, the potential of estimating flow cytometry DNA content in plant science has not been fully explored. Recent studies based on this method have revealed new phenomena in plant science (70)(71)(72) or new applications of the method (73). The present study highlights the use of FCM methodology, a powerful and precise tool for DNA content estimation, in plant reproduction biology.…”
Section: Application Of Fcss In Reproductive Biologymentioning
confidence: 72%
“…Recent studies based on this method have revealed new phenomena in plant science (70)(71)(72) or new applications of the method (73). Overall, the potential of estimating flow cytometry DNA content in plant science has not been fully explored.…”
Section: Application Of Fcss In Reproductive Biologymentioning
confidence: 99%
“…Cytometry data shows that endoreplication is not exponential but partial. In Vanilla planifolia, replication observed in each endocycle is not 2.00 but ~ 1.45, 1.6, 1.7, and 1.8 (Brown et al, 2017). The cumulative effect of this "strict partial endoreplication" leads to a loss of 41% of expected DNA content in 32C nuclei.…”
Section: Case Of Endoreplicationmentioning
confidence: 95%
“…One way to obtain nuclei from different cell cycle phases, with a higher purity than chemical synchronisation, is to isolate them by chopping and sorting by cytometry. The yield will be lower but sufficient to do downstream molecular biology experiments (Pirrello et al, 2014) or imaging (Bourdon et al, 2012;Brown et al, 2017). Beyond nuclei, cytometry technology allows chromosome sorting.…”
Section: Nuclei/chromosome Sortingmentioning
confidence: 99%